The Impact of the Construction of Large Reservoirs on the Cultural Landscape: A Case Study of the Shimen Reservoir, Taiwan - Li-Yu Chen; Wen-Zhe Hsieh; Rung-Jiun Chou (Land, 2021)
Reservoirs are large-scale water facilities with multiple functions, such as water supply, power generation, and tourism. This paper introduces the new community and cultural landscape formed by the indigenous people, engineers, workers who left their homes, and many migrating families at the Shimen Reservoir in Taoyuan, Taiwan, as an example. We analyzed how the community value of reservoir construction contributed to the development of the landscape through fieldwork, document review, and in-depth interviews. First, the new communities created to meet the needs of the immigrants influenced the surrounding environment and shaped a particular lifestyle. Secondly, new immigrants have formed a community consensus, and changes in the diet and natural landscape have promoted local tourism and affected the function of the reservoir. This study concludes that promoting local values through autonomous community action is a sustainable approach to community development. Tourism development with its symbiotic relationship with the reservoir can meet the needs of local socio-economic and cultural development. For sustainable development, a vulnerability study based on the Shimen Reservoir tourism is necessary.